Eosinophil extracellular traps activate type 2 innate lymphoid cells through stimulating airway epithelium in severe asthma - Choi, Youngwoo; Kim, Young‐Min; Lee, Hee‐Ra; Mun, Jiyeong; Sim, Soyoon; Lee, Dong‐Hyun; Pham, Duy Le; Kim, Seung‐Hyun; Shin, Yoo Seob; Lee, Seung‐Woo; Park, Hae‐Sim (Allergy (Copenhagen), 2020)
Background Activated eosinophils release extracellular traps (EETs), which contribute to airway inflammation in severe asthma (SA). However, the role of EETs in innate immunity has not yet been completely determined. The present study aimed to demonstrate the mechanism of airway inflammation in SA mediated by EETs. Methods Peripheral counts of EET+ eosinophils and type 2 innate lymphoid cells (ILC2s) were evaluated in patients with SA (n = 13), nonsevere asthma (NSA, n = 17), and healthy control subjects (HC, n = 8). To confirm the effect of EETs, airway hyperresponsiveness (AHR) and adapted/innate immune responses were assessed in mice. Furthermore, the effects of anti‐IL‐33/TSLP antibody were tested. Results The numbers of EET+ eosinophils and ILC2s were significantly elevated in SA, with a positive correlation between these two cells (r = .539, P < .001). When mice were injected with EETs, we observed significant increases in epithelium‐derived cytokines (IL‐1α, IL‐1β, CXCL‐1, CCL24, IL‐33, and TSLP) and eosinophil/neutrophil count in bronchoalveolar lavage fluid (BALF) as well as an increased proportion of IL‐5‐ or IL‐13‐producing ILC2s in the lungs. When Rag1−/− mice receiving ILC2s were treated with EETs, increased AHR and IL‐5/IL‐13 levels in BALF were noted, which were effectively suppressed by anti‐IL‐33 or anti‐TSLP antibody. Conclusion EETs could enhance innate and type 2 immune responses in SA, in which epithelium‐targeting biologics (anti‐IL‐33/TSLP antibody) may have a potential benefit. The numbers of EET+ eosinophils and type 2 innate lymphoid cells (ILC2s) are significantly elevated in severe asthma. EETs treatment in mice induces significant increase of epithelium‐derived cytokines (IL‐1α, IL‐1β, CXCL‐1, CCL24, IL‐33, and TSLP) and eosinophil/neutrophil count in bronchoalveolar lavage fluid. EETs activate IL‐5 or IL‐13‐producing ILC2s through stimulating airway epithelium.Abbreviations: EETs, Eosinophil extracellular traps; TSLP, Thymic stromal lymphopoietin